134k views
4 votes
PLZ HELP 70 POINTS!!!!!

Solve the following exponential equation for x. Show your work step by step.

5^(x+7) = (1/625)^(2x-13)

User Flumpb
by
4.9k points

2 Answers

1 vote

Hey there! the answer to this equation is


x=1/3125


Step-by-step explanation


You move all the terms to the left:


5^x-(1/625)^(2x-13)=0


Then add all the numbers altogether, and the variables too


5^x-(+1/625)^(2x-13)=0


Now get rid of the parentheses


5^x-1/625^2x-13=0


Multiply all of them by the denominator


5^x*625-1 .2x-13=0


Finally , move all terms to the left, and all other terms to the right

This should be your final answer

3125x=1


Hope this helped you and if im wrong, correct me.

User Arunbh Yashaswi
by
5.2k points
0 votes

5^(x+7)=(1/625)^(2x-13)


We move all terms to the left:


5^(x+7)-((1/625)^(2x-13))=0



Domain of the equation: 625)^(2x-13))!=0


x∈R



We add all the numbers together, and all the variables


5^(x+7)-((+1/625)^(2x-13))=0


We multiply all the terms by the denominator



(5^(x+7))*625)^(2x+1-13))-((=0


We add all the numbers together, and all the variables


(5^(x+7))*625)^(2x-12))-((=0


We add all the numbers together, and all the variables


(5^(x+7))*625)^(2x=0

not sure if this is right :/


User Matteo Ferla
by
5.4k points